The Beat to Read: A Cross-Lingual Link between Rhythmic Regularity Perception and Reading Skill - Bekius, Annike; Cope, Thomas E.; Grube, Manon (Frontiers in Human Neuroscience, 2016)
This work assesses one specific aspect of the relationship between auditory rhythm cognition and language skill: regularity perception. In a group of 26 adult participants, native speakers of 11 different native languages, we demonstrate a strong and significant correlation between the ability to detect a ‘roughly’ regular beat and rapid automatized naming (RAN) as a measure of language skill (Spearman’s rho, -0.47, p <0.01). This correlation remains significant after accounting for differences in non-verbal IQ (rho, -0.37, p <0.05), and musical expertise in addition (rho, -0.31, p <0.05). There was no such robust relationship for the ‘mirror image’ task of irregularity detection, i.e. the ability to detect ongoing small deviations from a regular beat. This dissociation in correlation was confirmed after accounting for shared variance between the two rhythm tasks. Whilst being consistent with the ‘shared resources model’ in terms of rhythm as a common basis of language and music, evolutionarily as well as in individual development, the results also document how two related rhythm processing abilities relate differentially to language skill. Specifically, the results support a universal relationship between rhythmic regularity detection and reading skill that is robust to accounting for differences in fluid intelligence and musical expertise, and transcends language-specific differences in speech rhythm.